2021
DOI: 10.1021/acsanm.1c00119
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Framework MIL-101(Fe) Nanoparticles Decorated with Ag Nanoparticles for Regulating the Photocatalytic Phenol Oxidation Pathway for Cr(VI) Reduction

Abstract: Photocatalysis is a promising technology to treat dilute phenol-Cr(VI) mixture, where photo-induced electrons are commonly thought of as the main active species for Cr(VI) reduction. However, it generally depends on the surface adsorption to achieve efficient electron transfer. Meanwhile, the possible contribution of reductive quinone derivatives oxidized from phenol to Cr(VI) reduction has been rarely explored. The key is to explicitly understand the relation between the phenol oxidation pathway and Cr(VI) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…The detection wavelength was 238 nm. The Cr (VI) concentration was detected using a typically colorimetric method at 540 nm, as proposed by previous study [32].…”
Section: Chemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The detection wavelength was 238 nm. The Cr (VI) concentration was detected using a typically colorimetric method at 540 nm, as proposed by previous study [32].…”
Section: Chemical Analysismentioning
confidence: 99%
“…Recently, it has been found that a rational complex of MOFs with various semiconductor nanoparticles is able to not only optimize the generation of active species but also boost catalytic performance. For instance, g-C 3 N 4 /MIL-101(Fe), g-C 3 N 4 /PDI@NH 2 -MIL-53(Fe), TiO 2 /MIL-100(Fe) and Ag/AgCl/MIL-101(Fe) have been designed and used as photocatalysts for the removal of Cr (VI) and organic pollutants, such as bisphenol A, tetracycline and carbamazepine [30][31][32][33]. However, to the best of our knowledge, there are still no reports on the synergetic removal of Cr (VI) and MC-LR.…”
Section: Introductionmentioning
confidence: 99%
“…TEM images of (a) MIL-101­(Fe), (b) 0.5% Ag/AgCl/MIL-101­(Fe), (c) 1% Ag/AgCl/MIL-101­(Fe), and (d) 2% Ag/AgCl/MIL-101­(Fe). Reprinted with permission from ref . Copyright 2021 American Chemical Society.…”
Section: Recent Progress In Mof-based Photocatalystsmentioning
confidence: 99%
“…Mechanism of the Cr (VI) photoreduction by Ag/AgCl/MIL-101­(Fe). Reprinted with permission from ref . Copyright 2021 American Chemical Society.…”
Section: Recent Progress In Mof-based Photocatalystsmentioning
confidence: 99%
“…The standard diphenylcarbazide (DPC) method was used to measure the concentration of Cr(VI). 44,45 Scavenging experiments were performed to investigate the influence of different active species during the photocatalytic process. 1.0 mmol L −1 ethylenediaminetetraacetic acid (EDTA), 1.0 mmol L −1 tert-butanol (BUOH), and 0.33 mmol L −1 benzoquinone (BQ) were utilized as scavengers of h + , hydroxyl radicals (˙OH), and superoxide radical anions (˙O 2 − ), respectively.…”
Section: Photocatalytic Activitymentioning
confidence: 99%